Wood anatomy chronologies of Scots pine in the foothills of the Western Sayan (Siberia) - Babushkina, Elena A.; Dergunov, Dmitry R.; Zharkov, Mikhail S.; Belokopytova, Liliana V.; Zhirnova, Dina F.; Yang, Bao; Liu, Jingjing; Peng, Xiaomei; Vaganov, Eugene A. (Journal of forestry research, 2024)
Recent methodological advances in quantitative wood anatomy have provided new insights into the climatic responses of radial growth at the scale of cell structure of tree rings. This study considered long-term chronologies of tracheid measurements, indexed by a novel approach to separate their specific climatic responses from signal recorded in cell production (closely reflected in tree-ring width). To fill gaps in understanding the impact of climate on conifer xylem structure, Scots pine ( Pinus sylvestris L.) trees > 200 years old were selected within the forest-steppe zone in southern Siberia. Such habitats undergo mild moisture deficits and the resulting climatic regulation of growth processes. Mean and maximum values of cell radial diameter and cell wall thickness were recorded for each tree ring. Despite a low level of climatogenic stress, components of cell chronologies independent of cambial activity were separated to obtain significant climatic signals revealing the timing of the specific stages of tracheid differentiation. Cell expansion lasted from mid-April to July and was impacted similarly to tree-ring width (stimulated by precipitation and stressed by heat), maximum cell size formed late June. A switch in the climatic responses of mean anatomical traits indicated transition to latewood in mid-July. Secondary wall deposition lasted until mid-September, suppressed by end of season temperatures. Generally, anatomical climatic responses were modulated by a less dry May and September compared with summer months.